Protective role of Taurine against mercuric chloride intoxicated rats - G. Jagadeesan, S. Sankar Samipillai (Recent Research in Science and Technology, 2009)
Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â The present study has been designed to investigate the influence of taurine on mercury intoxicated kidney tissue of rats (Rattus norvegicus). At sub-lethal dose of mercuric chloride (2mg/kg body weight) treatment,Ã‚Â creatinine, and blood urea nitrogen (BUN) and lipid peroxidation (LPO) contents were significantly increased in serum and kidney tissues respectively. And simultaneously, reduced glutathione (GSH) content, glutathione peroxidase (GPx), catalase (CAT) and superoxide dismutase (SOD) activities were significantly decreased due to rupture of kidney tissue caused by mercury poison. During the recovery period, mercury chloride intoxicated rats were again treated with taurine (50mg/kg body weight) for another 15 days. It shows the remarkable recovery of the animal from the adverse effect of mercury toxicity. An enhanced level of LPO content and altered level of antioxidant system were restored to near normal level in mercury intoxicated animals. The result suggested that taurine play a vital role to reduce the toxic effect of mercury in the kidney tissue of rats.Ã‚Â Ã‚Â